Generating Expectations: What Pediatric Rehabilitation Can Learn From Mental Health Literature. (4th March 2019) - Smart, Eric; Nalder, Emily; Rigby, Patty; King, Gillian
ABSTRACT: Family-Centered Care (FCC) represents the ideal service delivery approach in pediatric rehabilitation. Nonetheless, implementing FCC as intended in clinical settings continues to be hindered by knowledge gaps. One overlooked gap is our understanding of clients' therapy expectations. This perspective article synthesizes knowledge from the mental health services literature on strategies recommended to service providers for generating transparent and congruent therapy expectations with clients, and applies this knowledge to the pediatric rehabilitation literature, where this topic has been researched significantly less, for the purpose of improving FCC implementation. Dimensions of the Measure of Processes of Care, an assessment tool that measures clients' perceptions of the extent a service is family-centered, inform the organization of therapy expectation-generating strategies: (1) Providing Respectful and Supportive Care (assessing and validating clients' expectations); (2) General and Specific Information (foreshadowing therapy journeys, explaining treatment rationale, and conveying service provider qualifications); (3) Coordinated and Comprehensive Care (socializing clients to roles and reflecting on past socialization); and (4) Enabling and Partnership (applying a negotiation framework and fostering spaces safe to critique). Strategies can help pediatric rehabilitation service providers work with families to reframe unrealistic expectations, establish congruent beliefs supporting effective partnerships, and prevent possible disillusionment with therapy over time.